Library disasters preparedness of librarians in selected public and academic libraries - Ramirez, Maria Katrin C.; Santos, Daniel G. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
This study gathered information on the library disaster preparedness of four (4) prestigious public and academic libraries, namely: the Quezon City Public Library, the Marikina City Public Library, the Ateneo de Manila University Rizal Library, and the University of the Philippines Main Library.
The data on (1) the effects of disasters, (2) disaster prevention, (3) response to disasters, and (4) recovery from disasters were gathered from questionnaires accomplished by the librarians serving the four (4) institutions included in the study. Analysis was done to determine whether the answers were in accordance with the prescriptions of the IFLA Disaster Preparedness and Planning Manual.
This study showed that the librarians serving the respondent institutions (1) have sufficient knowledge of the effects of disasters, (2) have insufficient knowledge in the areas of disaster prevention, response and recovery due to (1) the absence of disaster preparedness plans, (b) minimal training on library disaster management, and (c) inadequate equipment to prevent/respond to or recover from disasters.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Emergency management; Academic libraries -- Philippines -- Quezon City; Public libraries -- Philippines -- Quezon City; Librarians -- Philippines -- Marikina City; Librarians -- Philippines -- Quezon City